ACL injury management: a comprehensive review of novel biotherapeutics - Yu, Xuezhi; Hu, Jiahui; Li, Yifan; Wen, Yu; Li, Bin (Frontiers in Bioengineering and Biotechnology, 2024)
The anterior cruciate ligament (ACL) is integral to the stability of the knee joint, serving to limit anterior tibial translation and regulate rotational movements. ACL injuries are among the most common and debilitating forms of knee trauma, often resulting in joint effusion, muscular atrophy, and diminished athletic capabilities. Despite the established efficacy of ACL reconstruction as the standard treatment, it is not uniformly successful. Consequently, there is a growing interest in novel biotherapeutic interventions as potential alternatives. This comprehensive review examines the latest advancements in ACL biotherapy, encompassing the application of hyaluronic acid, self-assembled short peptides, growth factors, stem cell therapy, gene therapy, platelet-rich plasma therapy, bone marrow aspirate concentrate cells, extracorporeal shock wave, electrical stimulation and cross bracing protocol. The collective aim of these innovative treatments is to facilitate the restoration of the ACL’s native biological and biomechanical integrity, with the ultimate goal of enhancing clinical outcomes and the functional recovery of affected individuals.